High-speed modal analysis of dynamic modal coupling in fiber laser oscillator - Chai, Junyu; Liu, Wenguang; Wang, Xiaolin; Zhou, Qiong; Xie, Kun; Wen, Yujun; Zhang, Jiangbin; Liu, Pengfei; Zhang, Hanwei; Zhang, Dan; Jiang, Zongfu; Zhao, Guomin (Frontiers in Physics, 2023)
Up till now, the spatial and temporal dynamics of transverse mode instability (TMI) in fiber laser oscillator have increasingly attracted a worldwide attention. Here, we develop a high-speed modal decomposition (MD) system to analyze the modal coupling for fiber laser oscillator above the TMI threshold. A set of angular-multiplexing transmission functions (TFs) are designed for simultaneous MD and monitoring the far-field beam profile. The TMI threshold of the deployed fiber laser oscillator is 181 W at a co-pumping power (CPP) of 279 W. As the CPP increases from 318 W to 397 W, the power fluctuations of the output laser become more drastic. The changes of the far-field beam profile and the centroid of far-field spot (COFFS) indicate an increased velocity of energy transfer between modes. The high-speed MD verifies above process and analyzes the modal components, indicating that the single cycle of modal coupling decreases from 11 ms to 4 ms. Otherwise, the strong mode coupling occurs between modes with relatively large weights. The high-speed MD provides a powerful tool to research the TMI effect.